Metastatic Relapse of Ewing Sarcoma with Parietal Bone Involvement and Intracranial Extension Following Euro-Ewing 2012 Protocol and Left Transfemoral Amputation - Bespalova, Vladyslava; Boridchenko, Sofiia; Boiko, Svitlana (The Ukrainian Scientific Medical Youth Journal, 2026)
Introduction. Ewing sarcoma is a highly aggressive malignant bone tumor associated with a high risk of relapse and metastatic spread, whereas skull and intracranial involvement remains rare and clinically challenging. Aim. The aim of this case report is to describe a late metastatic relapse of Ewing sarcoma presenting as a right parietal bone metastasis with intracranial extension 2.9 years after completion of Euro-Ewing 2012 protocol treatment and left transfemoral amputation, and to discuss implications for individualized post-remission surveillance. Materials and Methods. An 11-year-old patient initially achieved complete clinical remission after multimodal treatment for Ewing sarcoma of the left lower limb; however, due to emergency evacuation and subsequent treatment abroad after the beginning of the full-scale invasion of Ukraine, primary diagnostic documentation was limited, and regular surveillance imaging during remission was not performed according to the available history. In August 2025, the patient was admitted with persistent fever without an identifiable infectious source and subsequently developed a painless right parietal mass with headache. Brain CT and MRI revealed osteolytic destruction of the right parietal bone with a paraosseous soft-tissue component and intracranial parameningeal extension, while histopathological examination confirmed metastatic Ewing sarcoma. Results. Systemic staging demonstrated additional metastatic lesions in the left iliac bone and segment S5 of the right lung. Second-line treatment included high-dose ifosfamide-based chemotherapy, peripheral blood stem cell mobilization and collection, surgical resection of the cranial metastasis, and high-dose chemotherapy with autologous stem cell transplantation followed by referral for consolidative radiotherapy. After two cycles of chemotherapy, partial response was achieved according to RECIST 1.1 criteria, with reduction of the cranial, iliac, and pulmonary lesions; subsequent imaging showed complete regression of the pulmonary metastasis and stabilization of the iliac bone lesion. The cranial metastasis was resected with R0 margins, although isolated tumor cell elements were identified on the dural surface. Conclusions. This case illustrates that Ewing sarcoma may relapse after a prolonged remission period with atypical cranial and intracranial involvement and may initially present with nonspecific symptoms. Current follow-up strategies mainly focus on the primary site and chest imaging and may fail to detect rare metastatic localizations at an early stage. Brain MRI should not be interpreted as a routine requirement for all survivors; rather, it may be considered in selected patients with neurological symptoms, cranial complaints, unexplained fever without an identifiable source, or other high-risk clinical features. Further prospective studies are required to define standardized indications for neuroimaging during long-term follow-up of Ewing sarcoma survivors.